PENETAPAN KADAR FLAVONOID TOTAL EKSTRAK ETANOL JERAMI NANGKA (Artocarpus heterophyllus) SECARA SPEKTROFOTOMETRI-Visible - Marpaung, Jon Kennedy; Nasution, Zuhairiah; Thaib, Cut Masyithah; Siringoringo, Junisan (Jurnal Farmanesia, 2020)
Flavonoids are compounds consisting of 15 carbon atoms which are generally distributed in the plant world. Flavonoid compounds are a group of the largest phenolic compounds found in nature, these compounds are red, purple, and blue dyes as well as yellow dyes found in plants. This study aims to determine the total flavonoid content of the jackfruit straw ethanol extract by using the UV-VIS spectrophotometric method, this study includes sample preparation, simplicia phytochemical screening, and extract manufacture, then determine the total flavonoid content of the jackfruit straw ethanol extract which is equivalent to quercetin (Quercetin). Equivalent (QE)) using aluminum chloride reagent with a wavelength of 437 nm by Visible spectrophotometry. Based on the research conducted, the total flavonoid content of jackfruit straw extract determined by Visible spectrophotometry using aluminum chloride reagent was 114.7590± 52.1263 mg QE/g extract.